2018
DOI: 10.1002/epi4.12238
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the molecular mechanisms of genetic epilepsies using patient‐induced pluripotent stem cells

Abstract: SummaryResearch findings on the molecular mechanisms of epilepsy almost always originate from animal experiments, and the development of induced pluripotent stem cell (iPSC) technology allows the use of human cells with genetic defects for studying the molecular mechanisms of genetic epilepsy (GE) for the first time. With iPSC technology, terminally differentiated cells collected from GE patients with specific genetic etiologies can be differentiated into many relevant cell subtypes that carry all of the GE pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…These findings revealed the fundamental physiological mechanism of Epilepsy caused by SCN1A loss-of-function mutations 117 . Simultaneously, the iPSCs model research confirmed that astrocyte activation 118 - 120 , mitochondrial dysfunction 121 , 122 , and abnormal signaling pathway activity 123 , 124 were also important factors to the molecular mechanisms of GE 108 .…”
Section: Application Of Ipscs In Epilepsymentioning
confidence: 75%
See 1 more Smart Citation
“…These findings revealed the fundamental physiological mechanism of Epilepsy caused by SCN1A loss-of-function mutations 117 . Simultaneously, the iPSCs model research confirmed that astrocyte activation 118 - 120 , mitochondrial dysfunction 121 , 122 , and abnormal signaling pathway activity 123 , 124 were also important factors to the molecular mechanisms of GE 108 .…”
Section: Application Of Ipscs In Epilepsymentioning
confidence: 75%
“…Related neurodevelopmental HCN1, FGF12, SLC12A5, ARX, PCDH19, KCNA2, DENND5A, AARS, SCN8A, CDKL5, STXBP1, SCN1B, SLC1A2, PLCB1, DOCK7, TBC1D24, SCN2A, SPTAN1, SZT2, GABRB3, KCNQ2, GNAO1 and other genes can all lead to epileptic encephalopathy 106 , 107 . Epilepsy caused by single-gene mutations is the dominating reason for a variety of epilepsy syndromes 108 . Utilizing iPSCs models for genetic epilepsies (GE), gene mutations induced GE by altering the balance between neuronal excitation and inhibition, which is associated, among other factors, with neuronal developmental disturbances, ion channel abnormalities, and synaptic dysfunction 83 , 84 , 109 , 110 .…”
Section: Application Of Ipscs In Epilepsymentioning
confidence: 99%
“…Finally, dissociated cultures represent the only method for growing human-induced pluripotent stem cells (hiPSCs). These precursors can be differentiated into neurons, allowing the investigation of their molecular and electrophysiological properties (42,43). Most of all, they can be derived from patients for the purpose of specific drug development or cell therapies.…”
Section: "Traditional" Dissociated Cultures -Methods Applications and Spontaneous Activitymentioning
confidence: 99%
“…Childhood epileptic encephalopathies (CEEs) such as Dravet syndrome, Angelman syndrome, and Rett syndrome (RTT) are increasingly linked to specific genetic mutations. iPSC-derived neural cells, including GABAergic or glutamatergic neurons, have come to be a common tool to model epileptic disorders [80]. Astrocyte regulates neurotransmission by encasing thousands of synapses to form tripartite synapses between pre- and postsynaptic structures of two neurons and the surrounding astrocytic process [81].…”
Section: Modeling Neurological Disorders Using Human Psc-derived Amentioning
confidence: 99%